Artesania do cuidado: reverberações do corpo, do tempo e da experiência estética na terapia ocupacional - Oliveira, Ingrid Bergma da Silva (2016)
The aesthetic experience, of the body and of the time are vital issues because aside from operating brands, forge an existential territory, which is related to the possibility of create resistance through micropolitical actions on spaces increasingly homogenized. Find me in the field of Occupational Therapy in mental health, areas in which I live and where I speak about the relationship between madness and care. Motivated by affection and personal experiences in a time differentiated quality, with a very special relationship with the body and the aesthetic experience, i found myself authorized to discuss in such institutionalization times the Psychiatric Reform, another working mode, to care in which therapeutic devices are affected for personal resonances, existential experiences of who offer them. The demands and observations from the monitoring conducted with users attending in a CAPS in the city of Belém / PA, as well as teaching practice, helped to discuss the aesthetic experience of time and body in relation to mental health care. To account for basting this path, it was important to adopt a cartographic approach in the thesis. It s possible to observe that this cartography is permeated by practices that go through nondiagnostic setting, the importance of a subtle time and training space in psychosocial care, the inclusion of cultural elements in care practices, by an attentive listening to the personal stories of users, the emphasis in the approach of bodies, the intensity of actions between subjects as fuel bind and increased power of acting and everything it prints of attitude change before the treatment, elements that make up what nominate handmade care